Hardware location and clinical outcome in ulna shortening osteotomy - Megerle, Kai Oliver; Hellmich, Susanne; Germann, Günter; Sauerbier, Michael (Plastic and reconstructive surgery - global open, 2015)
Background: - The purpose of this study was to investigate the influence of plate location during ulna shortening osteotomy on the incidence of hardware irritation and clinical outcome. - Methods: - Forty patients (17 women, 23 men; mean age, 47 years) who underwent a shortening osteotomy of the ulna due to idiopathic ulna impaction syndrome were examined after a mean of 36 months. All complications and secondary procedures were extracted from the patients’ records. - Results: - The rate of hardware removal was higher in patients who had a dorsal placement of the plate in comparison with ulnar or palmar placements, although this difference was not statistically significant. Apart from hardware irritation, there were 4 nonunions, 1 secondary osteoarthritis of the distal radioulnar joint, and 1 case of chronic irritation of the dorsal branch of the ulnar nerve, which required secondary surgery. The incidence of secondary surgery other than hardware removal was not significantly related to the original location of the plate. - Conclusions: - Secondary surgery after ulnar shortening osteotomy is common. However, we found no difference in clinical outcomes based on plate location.
Gesehen am 10.06.2020